2020
DOI: 10.7759/cureus.9059
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Replacement Versus Fluid Restriction in COVID-19 Associated Hyponatremia

Abstract: Hyponatremia is one of the most frequently observed electrolyte abnormalities in coronavirus disease 2019 (COVID-19). Literature describes syndrome of inappropriate anti diuretic hormone (SIADH) as the mechanism of hyponatremia in COVID-19 requiring fluid restriction for management. However, it is important to rule out other etiologies of hyponatremia in such cases keeping in mind the effect of an alternate etiology on patient management and outcome. We present a case of hypovolemic hyponatremia in a patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
(14 reference statements)
1
15
0
2
Order By: Relevance
“…As stated earlier, she was given IV 3% saline and tolvaptan, both common ways to treat low sodium levels [10,13]. Our case also showed a W-curve [14] recovery in the patient as she was admitted to the hospital the second time in three weeks and was diagnosed as having post-COVID pneumonia and exhibited high CRP levels. The patient was treated with steroids, antacids, and antibiotics.…”
Section: Discussionsupporting
confidence: 70%
“…As stated earlier, she was given IV 3% saline and tolvaptan, both common ways to treat low sodium levels [10,13]. Our case also showed a W-curve [14] recovery in the patient as she was admitted to the hospital the second time in three weeks and was diagnosed as having post-COVID pneumonia and exhibited high CRP levels. The patient was treated with steroids, antacids, and antibiotics.…”
Section: Discussionsupporting
confidence: 70%
“…Frequent blood glucose and ketone body monitoring is mandatory in patients with COVID-19 and hyperglycaemia. Fluid and electrolyte management in patients with COVID-19 and impaired respiratory function should follow general recommendations 121 , 122 ; no specific guidance exists for fluid and electrolyte management in patients with diabetes mellitus and COVID-19.…”
Section: Use Of Antidiabetic Medicationsmentioning
confidence: 99%
“…COVID-19 is a disease with widely variable outcomes, among which 19% develop severe disease [2].Adverse clinical outcome correlates with multi-organ injury, maladaptive functions of the renin-angiotensin-aldosterone system and thirst and appetite abnormalities, all of which potentially disrupt water homeostasis [3]. A number of case reports describing hyponatraemia of various etiologies was initially published [4][5][6][7]. Later, a descriptive study of 16 patients with COVID-19-related hospitalization found 50% of them had hyponatraemia [8], whereas the HOPE study, an international registry of 4664 hospitalized COVID-19 patients, found that 20.5% and 3.7% had hyponatraemia and hypernatraemia, respectively [9]: both hyponatraemia and hypernatraemia were generally mild (130-134 mEq/l in 16.7%), severe hyponatraemia (<120 mEq/l) was found only in 0.4%.…”
mentioning
confidence: 99%